Antidepressant, antipsychotic and psychological interventions in subjects at high clinical risk for psychosis: OASIS 6-year naturalistic study. Issue 6 (22nd October 2014) - Fusar-Poli, P.; Frascarelli, M.; Valmaggia, L.; Byrne, M.; Stahl, D.; Rocchetti, M.; Codjoe, L.; Weinberg, L.; Tognin, S.; Xenaki, L.; McGuire, P.
Abstract : Background: Recent randomized controlled trials suggest some efficacy for focused interventions in subjects at high risk (HR) for psychosis. However, treating HR subjects within the real-world setting of prodromal services is hindered by several practical problems that can significantly make an impact on the effect of focused interventions. Method: All subjects referred to Outreach and Support in South London (OASIS) and diagnosed with a HR state in the period 2001–2012 were included ( n = 258). Exposure to focused interventions was correlated with sociodemographic and clinical characteristics at baseline. Their association with longitudinal clinical and functional outcomes was addressed at follow-up. Results: In a mean follow-up time of 6 years (s.d. = 2.5 years) a transition risk of 18% was observed. Of the sample, 33% were treated with cognitive behavioural therapy (CBT) only; 17% of subjects received antipsychotics (APs) in addition to CBT sessions. Another 17% of subjects were prescribed with antidepressants (ADs) in addition to CBT. Of the sample, 20% were exposed to a combination of interventions. Focused interventions had a significant relationship with transition to psychosis. The CBT + AD intervention was associated with a reduced risk of transition to psychosis, as compared with the CBT + AP intervention (hazards ratio = 0.129, 95% confidence interval 0.030–0.565, p = 0.007). Conclusions: There were differential associations with transition outcome for AD v. AP interventions in addition to CBT in HR subjects. These effects were not secondary to baseline differences in symptom severity.